PEMAHAMAN SUMBER DAYA MANUSIA DAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN SANGGAU - Risal (Program Studi Akuntansi Universitas Panca Bhakti, 2021)
This study aims to determine the effect of understanding human resources and the use of information technology on the quality of financial reports of the local government of Sanggau Regency.This study uses a quantitative approach, using primary data through a questionnaire. Respondents in this study were part of the financial managers of 25 SKPD Sanggau Regency. The variables in this study are the understanding of human resources and the use of information technology as independent variables and the quality of financial reports as the dependent variable. Data analysis used statistical method of multiple regression analysis. The results of hypothesis testing indicate that the understanding of human resources and the use of information technology has a positive effect on the quality of the financial reports of the Regional Government of Sanggau Regency. Keywords: Financial Statements, Human Resources, Information Technology.